2013
DOI: 10.1038/nrc3627
|View full text |Cite
|
Sign up to set email alerts
|

VEGF targets the tumour cell

Abstract: The function of vascular endothelial growth factor (VEGF) in cancer is not limited to angiogenesis and vascular permeability. VEGF-mediated signalling occurs in tumour cells, and this signalling contributes to key aspects of tumorigenesis, including the function of cancer stem cells and tumour initiation. In addition to VEGF receptor tyrosine kinases, the neuropilins are crucial for mediating the effects of VEGF on tumour cells, primarily because of their ability to regulate the function and the trafficking of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
822
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,055 publications
(874 citation statements)
references
References 188 publications
19
822
1
8
Order By: Relevance
“…103 In addition, VEGFA was also shown to directly act on tumor cells by promoting survival, proliferation, migration and invasion. 104 In a potential scenario radiotherapy induces hypoxia which in turn triggers tenascin-C and VEGFA expression. Each molecule/pathway alone as well as in conjunction may promote new blood vessel formation and tumor cell survival, thus promoting tumor regrowth, progression and metastasis post irradiation (Fig.…”
Section: Induction Of Tenascin-c Upon Radiotherapymentioning
confidence: 99%
“…103 In addition, VEGFA was also shown to directly act on tumor cells by promoting survival, proliferation, migration and invasion. 104 In a potential scenario radiotherapy induces hypoxia which in turn triggers tenascin-C and VEGFA expression. Each molecule/pathway alone as well as in conjunction may promote new blood vessel formation and tumor cell survival, thus promoting tumor regrowth, progression and metastasis post irradiation (Fig.…”
Section: Induction Of Tenascin-c Upon Radiotherapymentioning
confidence: 99%
“…Bevacizumab is a monoclonal antibody against VEGF that inhibits tumor angiogenesis and growth by blocking VEGF–VEGFR binding on endothelial cells, which is commonly used for the treatment of metastatic BC. To date, accumulating evidence has shown that VEGF is a multifunction molecule that affects a variety of cells in the tumor microenvironment, not only in endothelial cells 5. Thus, in the current study, we hypothesized that VEGF has a direct effect on BC cells that contributes to their malignant behavior.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, hypoxia induced by anti‐angiogenic therapy promotes selection of aggressive cancer cells17 and expansion of cancer stem cell pool 18. According to recent studies, VEGF is a multifunction molecule targeting not only endothelial cells but also other cell members in the tumor microenvironment, including cancer cells, fibroblasts, immune cells and more 5. However, VEGF's direct effect on cancer cells is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies revealed that VEGF165 was highly expressed in breast cancer tissues compared with adjacent tissues (23,24). RT-qPCR experiments demonstrated that four isoforms of VEGF were expressed in human breast cancer tissues, including VEGF121, VEGF145, VEGF165 and VEGF189, being VEGF165 the most abundant one (25). In addition, previous studies demonstrated that VEGF165 fused to GFP at its C-terminus was secreted and biologically active (26).…”
Section: Discussionmentioning
confidence: 99%